Roles of Actors in Palm Oil Value Chain: a Paradox - Hidayati, Firda; Noor, Irwan; Amiruddin, Akhmad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Process of globalization has added pressure to smallholder palm oil in world palm oil producers countries. The globalization, however, create opportunities for small palm oil holders to benefit from it whenever they are able to collaborate proportionally with other actors. In order to do so, this study is aimed to elaborate the current value chain and typology of smallholders to establish the suitable collaboration schema.Â The finding showed that although there is imperfect quality of role, the variety of actors involved make smallholders found a better role. The PTPN VIII Kertayaja (State-Owned Enterprises (SOE) should be able to gain benefit and opportunities from suggestion use of the collaboration with other actors within the value chain.Â However, it is the role of SOE that act as state fiscal-revenue collector as well as maintaining status quo and having coercive power but it makes them complacent it and neglect to achieve sustainability role in empowering farmers. On the other hand, willingness to maximize the benefits created from the transaction has led head of village, private enterprises, collectors, sellers and transporters to find the most innovative way to help the small plantation owner to ease the challenges and maximize their roles in adding value to the chain.